Influence of Rupiah Exchange Rate on Indonesia’s Economic Growth: Literature Study - Silaban, Sella; Aadilah, Hilmi; Matondang, Khairani (PT. Riset Press International, 2023)
In the international economy, the exchange rate has an important role as a transaction tool. Its existence clearly affects the economy of a country both nationally and internationally. In Indonesia, the rupiah exchange rate is pegged to the US dollar, because international trade is dominated by transactions in US dollars. The increase in the rupiah exchange rate caused the rupiah to depreciate against the US dollar. This study aims to determine how the effect of the rupiah exchange rate on Indonesia's economic growth every year. This research is a qualitative descriptive research through a review of literature studies originating from journals, books and sources of accurate information. From the review of literature studies it is known that the variable exchange rate of the rupiah against foreign currencies has a significant effect and has a negative sign. This is evidenced by the growth rate of Gross Domestic Product (GDP) compared to the rupiah exchange rate. This means that when the rupiah exchange rate depreciates (the dollar appreciates), economic growth will decrease. And conversely if the rupiah exchange rate appreciates (the dollar depreciates) it will cause economic growth to increase.